Carbapenem-resistant Enterobacterales infection and colonization in patients with severe burns: a retrospective cohort study in a single burn center - Myongjin Kim; Kibum Jeon; Dohern Kym; Jinsun Jung; Yu Jin Jang; Seung Beom Han (Antimicrobial Resistance and Infection Control)
Abstract Background Clinical characteristics and outcomes of carbapenem-resistant Enterobacterales (CRE) infection and colonization have rarely been reported in patients with severe burns, who are prone to severe bacterial infections. This study aimed to evaluate clinical characteristics and outcomes of CRE infection and colonization in patients with severe burns. Methods The characteristics of 106 episodes of CRE acquisition (infection or colonization) in 98 patients with severe burns were evaluated by a retrospective medical record review. The duration of rectal CRE colonization and its associated factors were determined in the survived patients. Results Five (4.7%) of the CRE acquisitions were identified on admission, and the remaining 101 (95.3%) were identified at a median of 11 days (range 2–75 days) after admission. Klebsiella pneumoniae represented 73.6% of the isolated CRE strains, and carbapenemase-producing CRE (CP-CRE) were identified in 70.8% of the isolates. Mortality was associated with an abbreviated burn severity index (ABSI) score ≥ 10 (p < 0.001) and previous carbapenem-resistant bacterial acquisition (protective, p = 0.010). For the 58 episodes of CRE acquisition in the survived patients, eradication of rectal CRE colonization was identified in 39 (67.2%) at a median of 64 days (range 10–434 days) after acquisition. CP-CRE strains were associated with prolonged rectal CRE colonization (p < 0.001). Conclusions The characteristics of CRE infection and colonization in patients with severe burns were similar to those in general critical patients. Enhanced infection prevention and control measures should be considered for patients with severe burns of an ABSI score ≥ 10 and those with CP-CRE.